Synchronous occurrence of papillary thyroid carcinoma and solitary fibrous tumor of the thyroid: a case report - Maissa Ben Thayer; Imen Helal; Raoueh Hedhli; Emna Rejeb; Fatma Khanchel; Ehsen Ben Brahim; Raja Jouini; Aschraf Chadli-Debbiche (Journal of Medical Case Reports)
Abstract Background Solitary fibrous tumors (SFT) are ubiquitous mesenchymal neoplasms of intermediate malignant potential. SFTs of the head and neck are rare, representing less than 0.1% of all SFTs. Solitary fibrous tumors of the thyroid (SFTT) are even rarer. Only 49 cases of SFTTs have been documented in the literature, with just two cases being synchronous with papillary thyroid carcinoma (PTC). By presenting a synchronous PTC and SFTT case, we aim to review the clinical presentation, diagnostic challenges, histopathological characteristics, and management strategies associated with this unusual co-occurrence. Case presentation A 46-year-old North African female patient with no prior medical history presented with a year-long, indwelling cervical swelling. Cervical ultrasound revealed two nodules in the right thyroid lobe and one nodule in the left thyroid lobe. The first right thyroid nodule, measuring 50 mm, is classified as European Thyroid Imaging and Reporting Data System (EU-TIRADS) III. The second right thyroid nodule, measuring 15 mm, and the 25 mm left thyroid nodule were classified as EU-TIRADS IV. A total thyroidectomy with bilateral lymphadenectomy was performed. Microscopic examination revealed that the left nodule and right nodule measuring 15 mm corresponded to invasive PTCs. The second nodule in the right lobe corresponded to a proliferation of spindle cells arranged in sheets and wavy or storiform bundles with a hemangiopericytoma-like vascular pattern. The spindle cells had indistinct boundaries with elongated non-atypical nuclei. There was no mitosis. On immunochemistry, the spindle cells showed strong and diffuse positivity for CD34 and CD99. They are negative for smooth muscle actin, S100, and cytokeratin. It was then confirmed to be an SFTT case. The final diagnosis was of synchronous PTC and SFTT. Conclusion We presented the third case of synchronous PTC and SFTT. The co-occurrence of these tumors is likely incidental. However, further studies are needed to assess the physiopathology and molecular alterations of this association.